Application of multi-pulse optical imaging to measure evolution of laser-produced counter-streaming flows - 袁大伟 李玉同 朱保君 李彦霏 仲佳勇 魏会冈 刘畅 原晓霞 张喆 梁贵云 王菲鹿 李芳 赵家瑞 华能 朱宝强 朱健强 江少恩 杜凯 丁永坤 赵刚 张杰 (Chinese physics B, 2017)
A counter-streaming flow system is a test-bed to investigate the astrophysical collisionless shock（CS） formation in the laboratory. Electrostatic/electromagnetic instabilities, competitively growing in the system and exciting the CS formation, are sensitive to the flows parameters. One of the most important parameters is the velocity, determining what kind of instability contributes to the shock formation. Here we successfully measure the evolution of the counter-streaming flows within one shot using a multi-pulses imaging diagnostic technique. With the technique, the average velocity of the high-density-part（ne ≥ 8–9 × 10^19cm^-3） of the flow is directly measured to be of ～ 10^6cm/s between 7 ns and 17 ns.Meanwhile, the average velocity of the low-density-part（ne ≤ 2 × 10^19cm^-3） can be estimated as ～ 10^7cm/s. The experimental results show that a collisionless shock is formed during the low-density-part of the flow interacting with each other.